Factors associated with adherence to antiretroviral therapy in HIV-infected patients in Kathmandu District, Nepal - Shigdel R (Dove Medical Press, 2014)
Rajesh Shigdel,1 Elise Klouman,2 Anita Bhandari,2 Luai A Ahmed11Department of Health and Care Sciences, 2Department of Community Medicine, Faculty of Health Sciences, UiT The Arctic University of Norway, Tromsø, NorwayPurpose: There are a high number of HIV-infected patients receiving antiretroviral therapy (ART) in the Kathmandu District of Nepal, but information on adherence and factors influencing it are scarce in this population. The present study aimed to estimate ART adherence among HIV-infected patients in the Kathmandu District of Nepal, and to determine the factors associated with ART adherence.Patients and methods: This study included 316 HIV-infected patients attending three ART centers in the Kathmandu District. Information on sociodemographic characteristics, socioeconomic status, and ART use for the previous 7 days was collected via interview. Participants were considered adherent if they reported taking ≥95% of their ART as prescribed. The association between explanatory variables and ART adherence was measured using logistic regression and reported as odds ratios (OR) with 95% confidence intervals (CI).Results: Male participants accounted for 64.6% (n=204). Overall ART adherence was 86.7%. ART adherence in men and women were 84.3% and 91.1%, respectively. Age (OR 1.04; 95% CI 1.00–1.09), travel time to ART centers (OR 1.38; 95% CI 1.12–1.71), history of illegal drug use (OR 3.98; 95% CI 1.71–9.24), and adverse effects (OR 4.88; 95% CI 1.09–21.8), were all independently and negatively associated with ART adherence. Use of reminder tools (OR 3.45; 95% CI 1.33–8.91) was independently and positively associated with ART adherence.Conclusion: The observed ART adherence in this study is encouraging. Travel time to ART centers, self-reported adverse effects, illegal drug use, and not using reminder tools were the major determinants of ART adherence. Interventions that take these factors into account could further improve ART adherence.Keywords: ART, adherence, HIV patients, AIDS patients, Asia, Nepal